Cerebral Small Vessel Disease, Risk Factors, and Cognition in Tenants of Precarious Housing. Issue 11 (November 2020) - Zhou, Lily W.; Panenka, William J.; Al-Momen, Ghadeer; Gicas, Kristina M.; Thornton, Allen E.; Jones, Andrea A.; Woodward, Melissa; Heran, Manraj K.S.; Vertinsky, A. Talia; Su, Wayne; Barr, Alasdair M.; MacEwan, G. William; et al.
Abstract : Background and Purpose: We aim to describe the burden, characteristics, and cognitive associations of cerebral small vessel disease in a Canadian sample living with multimorbidity in precarious housing. Methods: Participants received T1, T2-fluid-attenuated inversion recovery, and susceptibility-weighted imaging 3T magnetic resonance imaging sequences and comprehensive clinical, laboratory, and cognitive assessments. Cerebral small vessel disease burden was characterized using a modified Small Vessel Disease (mSVD) score. One point each was given for moderate-severe white matter hyperintensities, ≥1 cerebral microbleeds, and ≥1 lacune. Multivariable regression explored associations between mSVD score, risk factors, and cognitive performance. Results: Median age of the 228 participants (77% male) was 44.7 years (range, 23.3–63.2). In n=188 participants with consistent good quality magnetic resonance imaging sequences, mSVD scores were 0 (n=127, 68%), 1 (n=50, 27%), and 2 (n=11, 6%). Overall, one-third had an mSVD ≥1 n=61 (32%); this proportion was unchanged when adding participants with missing sequences n=72/228 (32%). The most prevalent feature was white matter hyperintensities 53/218 (24%) then cerebral microbleed 16/191 (8%) and lacunes 16/228 (7%). Older age (odds ratio, 1.10 [95% CI, 1.05–1.15], P <0.001), higher diastolic blood pressure (odds ratio, 1.05 [95% CI, 1.01–1.09], P =0.008), and a history of injection drug use (odds ratio, 3.13 [95% CI, 1.07–9.16], P =0.037) had significant independent associations with a mSVD score of ≥1 in multivariable analysis. mSVD ≥1 was associated with lower performance on tests of verbal memory, sustained attention, and decision-making, contributing 4% to 5% of the variance in each cognitive domain. Conclusions: The 32% prevalence of cerebral small vessel disease in this young, socially marginalized cohort was higher than expected for age and was associated with poorer cognitive performance. Abstract : Supplemental Digital Content is available in the text.